Propranolol disposition in patients with hepatosplenic schistosomiasis. - Homeida, M M (1987)
Eight Sudanese patients with hepatosplenic schistosomiasis and seven Sudanese controls were administered a single oral dose of long acting (LA), propranolol 160 mg; blood propranolol levels were measured at regular intervals for 12 h using g.l.c. In patients with hepatosplenic schistosomiasis, propranolol blood concentrations were greater (P less than 0.05) at all time intervals, Cmax 63.5 (29-143) ng ml-1 (median and range) than controls Cmax 23 (12-37) ng ml-1. Median AUC0-12 was also greater (P less than 0.05) (533 and 218 ng ml-1 h respectively), tmax were not significantly different. In patients and controls prior to treatment, standing heart rate (77.5 (60-110), 72 (68-74) beats min-1) systolic (120 (105-150), 110 (100-120) mm Hg) and diastolic blood pressure (75 (60-90), 70 (60-80) mm Hg) were not significantly different. However following propranolol administration a reduction (P less than 0.05) occurred in both systolic (median 20 mm Hg) and diastolic (median 12.5 mm Hg) blood pressure in the patients compared with controls. Heart rate was reduced by a median of 10 beats min-1 in both groups. These observations indicate that propranolol bioavailability in patients with hepatosplenic schistosomiasis is increased possibly due to reduced presystemic extraction.